Innovation in Medical Education: Teaching Medical Devices via Curricular Co-Creation - Vuk Uskokovic (Future of Medical Education Journal)
Background: Teaching medical devices presents the pinnacle of interdisciplinary educational efforts. To thoroughly cover this complex topic in a single course, it is required to encompass the principles of science, engineering, biology, medicine, pharmacy, economy, politics and humanities, all under one hat. Challenges faced by educators in the attempt to accomplish this naturally call for the exploration of innovative pedagogic strategies to be implemented in teaching this extremely broad subject.Method: Here I share with the readers a new instructional method I devised after a decade of coping with these challenges. The method is based on collective in-class presentations and discussions centered around the hierarchy of Bloom’s learning taxonomy and the students’ individual choices of medical devices for elaboration and analysis. Results: The method was overwhelmingly well accepted by the students, who have expressed a statistically significant preference for it over the traditional didactic method involving the instructor’s own choice of the material. Specifically, students’ mean (SD) satisfaction with teaching on the scale of 1.00 – 5.00 increased from 3.89 (0.78) for the instructor-centered didactics to 4.55 (0.82), 4.88 (0.34) and 4.91 (0.30) for this new pedagogic model implemented in the semesters of fall 2021, fall 2022 and fall 2023, respectively.Conclusion: The method shared here is particularly well suited for audacious instructors who feel comfortable improvising the topics and those who are broadly educated and well versed in a variety of subjects.